Compensatory branching morphogenesis of stalk cells in the Drosophila trachea. - Francis, D.; Ghabrial, A.S. (Development, 2015)
Tubes are essential for nutrient transport and gas exchange in multicellular eukaryotes, but how connections between different tube types are maintained over time is unknown. In the Drosophila tracheal system, mutations in oak gall (okg) and conjoined (cnj) confer identical defects, including late onset blockage near the terminal cell-stalk cell junction and the ectopic extension of autocellular, seamed tubes into the terminal cell. We determined that okg and cnj encode the E and G subunits of the vacuolar ATPase (vATPase) and showed that both the V0 and V1 domains are required for terminal cell morphogenesis. Remarkably, the ectopic seamed tubes running along vATPase-deficient terminal cells belonged to the neighboring stalk cells. All vATPase-deficient tracheal cells had reduced apical domains and terminal cells displayed mislocalized apical proteins. Consistent with recent reports that the mTOR and vATPase pathways intersect, we found that mTOR pathway mutants phenocopied okg and cnj. Furthermore, terminal cells depleted for the apical determinants Par6 or aPKC had identical ectopic seamed tube defects. We thus identify a novel mechanism of compensatory branching in which stalk cells extend autocellular tubes into neighboring terminal cells with undersized apical domains. This compensatory branching also occurs in response to injury, with damaged terminal cells being rapidly invaded by their stalk cell neighbor.